Economia, ciência e a imagem do Amazonas: articulações e propaganda em tempos de crise econômica (1920-1930) - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This paper presents through a historical approach on the Amazon the years 1920 to 1930, setting up a state of the visual and commercial image upon the joints and propagandistic actions built within the relationships between economic sectors and scientific segments, identified a series of visual sources written and collected during the investigation. Through the analysis of sources and literature readings, we realize that the economic sectors and the state government, concerned about the economic life that had increasingly troubled because of the gumífera economic crisis; and scientific segments, interested in new research and discoveries in the vast Amazonian scenario that aroused in them an interest exploration and studies; were the subjects that mediated actions and alliances that resulted in a picture of a thriving Amazon, promising and with great economic potential, this being disseminated through events, photographs, reports, periodicals and magazines, becoming the factor analyzed in the process of construction
Keywords: Crise econômica; Economia amazonense; CIÊNCIAS HUMANAS: HISTÓRIA